Isolation and molecular identification of canine bufavirus: a novel enteric pathogen of dogs - Acar, Gulizar; Yoru, Hayrunnisa Bostan; Polat, Erdal; Aslan, Ahsen Nisa; Aydin, Hakan; Timurkan, Mehmet Ozkan (Springer Wien, 2025)
Canine bufavirus (CBuV) was initially detected in dogs with respiratory symptoms and later identified in fecal samples, suggesting that it could be an enteric pathogen. Several studies have shown that CBuV can be present in both healthy and diarrheic dogs, raising questions about whether CBuV is a primary enteric pathogen. In this study, we identified, isolated, and characterized CBuV from swab samples from dogs. A total of 119 samples from diarrheic dogs were analyzed by PCR, targeting a portion of the VP2 gene of CBuV. CBuV was detected in five dogs (4.2%). For virus isolation, CBuV-positive samples were inoculated onto an MDCK cell culture, and CPE was observed for one sample, which was tested for CBuV as well as other frequently detected enteric pathogens (canine distemper virus, canine parvovirus type 2, and canine coronavirus), but CBuV was the only virus detected. Phylogenetic analysis indicated that the CBuV isolates from this study are closely related to strains from China and India. The detection of CBuV in this study suggests that it might play a distinct role in canine diarrhea. Further studies are needed to investigate its genetic characteristics, epidemiology, and biological significance.
Keywords: Diarrhea; Feces